El ferrocarril orense y su aprovechamiento turístico. - Armijos Prado, Angie Dayana (My University, 2020)
The history of the railroad as a means of transport between the Sierra region and Costa has been losing importance in several cities due to industrialization. However, through the Ecuadorian cruise train project it was possible to promote and develop the tourism sector on a large scale, where the beneficiaries were many. The greatest achievement of this project was to leave the name of Ecuador high, making itself known worldwide. The Orense train, a symbol of unity that through its railway system united the most important sites of the province for the transfer and export of products. Today, their conditions are not optimal and the population does not know what the railroad represented for the development of the towns. Therefore, it has been proposed to design a tourist railway between the old stations of Playas and Piedras to promote the use of the existing industrial infrastructure. The research process is based on exploratory research, to analyze factors that intervene in the objectivity of the case study. The data collected are qualitative in nature and focus on descriptive aspects. Two research methods, theoretical and empirical-inductive, were used for the research process. In the theoretical part was carried out the bibliographic review of the various secondary sources such as scientific articles, books and news. While in the empirical-inductive part, several methodological instruments were applied to obtain information. The most relevant was a digital survey aimed at the population of the province of El Oro, where the sample was 384. The results obtained reflected the acceptance of the proposal, the ignorance of the history of the Orense railroad and at the same time the interest to know more about this topic. In addition, an interview was also conducted with the authorities, which provided answers to a number of questions raised at the beginning of the investigation regarding the conditions in which the object of study was found. In addition, in order to measure environmental impacts and from this establish mitigation measures, a Leopold Matrix was made, also known as the cause - effect matrix. It was concluded that the project is viable in the social, technical and environmental dimensions. In the economic dimension, the same cannot be said because of the lack of budget on the part of the regulatory body due to the health emergency that the country is going through due to the spread of Covid-19. The proposal is considered to be beneficial for the development of the tourism sector of the province due to the increase and diversification of the supply. To this end, it is planned to keep the locomotives in optimum conditions for their exhibition, to build a section of railway route and to request a railway for their circulation. The realization of this project requires the support of the provincial authorities and multidisciplinary team. To this is added the role of society to take care of what belongs to them and with what they identify.
La historia del ferrocarril como medio de transporte entre la región Sierra y Costa ha ido perdiendo importancia en varias ciudades debido a la industrialización. Sin embargo, a través del proyecto del tren crucero ecuatoriano se logró fomentar y desarrollar el sector turístico a gran escala, donde los beneficiarios fueron muchos. El logro más grande de este fue proyecto fue dejar el nombre de Ecuador en alto, dándose a conocer a nivel mundial. El tren orense, un símbolo de la unidad que a través de su sistema ferroviario unió a los sitios más importantes de la provincia para el traslado y exportación de productos. Hoy en día, sus condiciones no son óptimas y la población desconoce lo que representó el ferrocarril para el desarrollo de los pueblos. Por ello se ha planteado diseñar una ruta férrea turística entre las antiguas estaciones de Playas y Piedras para fomentar el aprovechamiento de la infraestructura industrial existente. El proceso investigativo se fundamenta en una investigación exploratoria, para analizar factores que intervienen en la objetividad del caso de estudio. Los datos recopilados son de carácter cualitativo y se centra en aspectos descriptivos. Para el proceso investigativo se emplearon dos métodos de investigación, teórico y empírico-inductivo. En la parte teórica se llevó a cabo la revisión bibliográfica de las diversas fuentes secundarias tales como artículos científicos, libros y noticias. Mientras que en la parte empírica-inductiva se aplicó varios instrumentos metodológicos para la obtención de información. La más relevante fue una encuesta digital dirigida a la población de la provincia de El Oro, donde la muestra fue 384. Los resultados obtenidos reflejaron la aceptación de la propuesta, el desconocimiento de la historia del ferrocarril orense y a la vez el interés por saber más sobre ese tema. Por otro lado, también se realizó una entrevista dirigida a las autoridades, la cual dio respuestas a una serie de interrogantes planteadas al principio de la investigación respecto a las condiciones en la que se encontraba el objeto de estudio. Además, para poder medir los impactos ambientales y a partir de ello establecer las medidas de mitigación se realizó una Matriz de Leopold, también conocida como la matriz causa - efecto. Como conclusión se obtuvo que el proyecto es viable en la dimensión social, técnica y ambiental. En la dimensión económica no se puede manifestar lo mismo debido a la falta de presupuesto por parte del organismo regulador por causa de la emergencia sanitaria que atraviesa el país debido a la propagación de Covid-19. Se estima que la propuesta sea beneficiosa para el desarrollo del sector turístico de la provincia debido al incremento y diversificación de la oferta. Para ello se proyecta conservar las locomotoras en óptimas condiciones para su exposición, construir un tramo de ruta férrea y solicitar un ferrocarril en comodato para su circulación. La realización de este proyecto requiere del apoyo de las autoridades provinciales y equipo multidisciplinario. A esto se suma el rol de la sociedad de cuidar lo que les pertenece y con lo que se identifican.
Keywords: PATRIMONIO CULTURAL; FERROCARRIL; HISTORIA; VALOR; INDUSTRIALIZACIÓN